As relações de substituição entre cadernetas de poupança e fundos de investimento. - Silva, Maria Aparecida Lucas da (Universidade Federal de São Carlos, 2013)
This thesis aims to investigate the relations of substitution between Saving Accounts and DI Funds during the period of December 2004 and December 2012. The Brazilian basic interest rate SELIC rate has reduced over 10 percentage points during this period. Such a downward movement affected the returns on financial assets, i.e., their "prices", defined as opportunity costs in relation to the SELIC rate. The hypothesis is that substitution relationship between Saving Accounts and DI Funds have changed over time due to different levels of SELIC rate prevailing during the analyzed period. The dual approach and the nonlinear seemingly unrelated equations model (INSUR model) are used to estimate the demands via Translog functional form. Morishima elasticities of substitution are calculated in seven points of the sample in order to measure the substitution effect over the time and to evaluate possible asymmetry of elasticities. The results confirm the hypothesis that different levels of SELIC have engendered different patterns of relations of substitution between the analyzed assets. The conclusion is that the anew relations of substitution have expanded the role of Saving Accounts as instrument of private savings over DI Funds.
The substitution relations between saving accounts and investiment funds
Keywords: política monetária - Brasil; investimentos; análise de desempenho; cadernetas de poupança; elasticidades de substituição de Morishima; Fundos DI; INSUR; SELIC; Translog; DI Funds; INSUR; Morishima Elasticity of Substitution; saving accounts; SELIC; Translog; CIENCIAS SOCIAIS APLICADAS::ECONOMIA